An anatomy of the Phillips curve - Marika Karanassou; Dennis J. Snower (Queen Mary University of London, Department of Economics, 2002)
The paper examines how the long-run inflation-unemployment tradeoff depends on the degree to which wage-price decisions are backward- versus forward-looking. When economic agents, facing time-contingent, staggered nominal contracts, have a positive rate of time preference, the current wage and price levels depend more heavily on past variables (e.g. past wages and prices) than on future variables. Consequently, the long-run Philipps curvebecomes downward-sloping and, indeed, quite flat for plausible parameter values. This paper provides an intuitive account of how this long-run Philipps curve arises.
Keywords: J3; E2; E5; E3; 330; Inflation-unemployment tradeoff; wage-price staggering; monetary policy; forward- and backward looking wage-price behavior; Phillips-Kurve; Theorie